Women workers, migration and family in Sarawak - Hew, Cheung Sim (RoutledgeCurzon, 2003)
Based on research among the women of the Bidayuh people in Sarawak, all of them first generation migrant wage workers, this book explores the changes in women's lifestyles from traditional rural lifestyles to modern urban ones.